Land Dispute Settlement of Laba Pura Tanah Ayu in Sibang Gede, Badung Regency - I Putu Suantika; I Made Suwitra; I Made Sepud (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2018)
Land is one of the productive sources that play a very important role for humans because of its function as one of the sources of life. Land has become a vulnerable source of disputes between people, especially of the tenure or ownership over it. This study was carried out to reveal how the conversion of the land function of Tanah Ayu Pura Tanah in Badung Regency is made and to describe how the dispute in making a certificate for the land is carried out. To achieve the objectives of this study, empirical juridical method was applied by making use of the statute approach, conceptual approach, and case approach. Data in the form of primary and secondary data were collected by applying note-taking technique and documentation technique. Data analysis was carried out through the application of descriptive qualitative data analysis methods. From the results of the data analysis, it is found that the conversion of land of Laba Pura tanah ayu in Badung Regency is begun with the issuance of certificate, that is the new Notification of Tax Due (SPPT) for one plot of land and for two certificates of two plots of land that are not at the same location. In fact, the SPPT issued was not for land located in the Laba Pura tanah ayu. There has never been an agreement from the comparator in the issuance of the said land certificate, so that the certificate issued is legally defective. The settlement of the dispute over the issuance of the land certificate of Laba Pura tanah ayu is carried out through deliberation at the Office of the National Land Agency. If the dispute cannot be settled under government assistance, it shall be done through court institution.